The Preliminary Exploration of Multimedia Effects in Sculpture Creation Inspired by Maslow’s Hierarchy of Needs - Xing Yu Liu; Kin Meng Cheng (Proceedings, 2022)
Due to the limits of conventional sculpting, some artists may be unable to express themselves creatively. The research question is therefore posed: What are the factors that influence the use of multimedia effects in sculpture creation and Maslow’s hierarchy of needs? The research objective of was to identify the factors that influence the use of multimedia effects in sculpture creation and Maslow’s hierarchy of needs and to develop new creative methods for sculptors. The study used the purposive sampling method to invite six traditional sculpture artists and six multimedia sculpture artists to participate in interviews in an online format. Six factors were obtained from the analysis.